2015
DOI: 10.1039/c5ra11201j
|View full text |Cite
|
Sign up to set email alerts
|

Fixed dose combination therapy loperamide and niacin ameliorates diethylnitrosamine-induced liver carcinogenesis in albino Wistar rats

Abstract: BackgroundHepatocellular Carcinoma (HCC) is among the most lethal cancers (five-year survival rates under 11%), which makes it the third most frequent cause of cancer related deaths in men and sixth in women. Still there are limited treatments available for majority of HCC at advanced stages. Systemic chemotherapy for advanced hepatocellular carcinomas, either as single-agent therapy or in combination, radiofrequency ablation or recently introduced tyrosine kinase inhibitors, e.g. sorafenib are some to bank up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Its effect on intestinal motility is well established. [15] The apoptosisinducing activity of Loperamide has also been reported by the researchers [16,17] may be by promoting caspase 3 activity. In this hypothesis we are trying to evaluate the liver function profile altered or restored by the synergistic activity by Loperamide and Niacin.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Its effect on intestinal motility is well established. [15] The apoptosisinducing activity of Loperamide has also been reported by the researchers [16,17] may be by promoting caspase 3 activity. In this hypothesis we are trying to evaluate the liver function profile altered or restored by the synergistic activity by Loperamide and Niacin.…”
Section: Introductionsupporting
confidence: 52%
“…These enzyme generally elevate and squeeze out of the liver cells during necrosis or hepatitis whether chronic hepatitis or cholestitis hepatitis. It has also been observed and established by the researchers that SGPT, SGOT, serum bilirubin level elevates significantly after DENA exposure in the experimental animals [19,17] . In present study serum SGPT and SGOT levels elevated significantly (p<0.001) in all groups exposed to DENA as compared to the NC group.…”
Section: Discussionmentioning
confidence: 72%
“…The hepatic parameters, namely alkaline phosphatase (AST), aspartate aminotransferase (AST), alanine transaminase (ALT); serum renal parameters, including blood urea nitrogen (BUN), total protein, creatinine, albumin; lipid parameters, such as total cholesterol (TC), high density lipoprotein (HDL), triglyceride (TG), very low density lipoprotein (VLDL) and, low density lipoprotein (LDL), were scrutinized using commercially available diagnostic kits. The atherogenic index and coronary risk index were scrutinized as per the given formula: [24][25][26][27][28][29][30][31] Inammatory and pro-inammatory mediators Pro-inammatory cytokines, namely interleukin-6 (IL-6), tumor necrosis factor-a (TNF-a), and inammatory mediators, such as C-reactive protein (CRP), were also estimated as per the instructions in the available commercial kits.…”
Section: Biochemical Parametersmentioning
confidence: 99%
“…27 Lesions in liver tissues have been reported earlier to be due to elevated levels of liver enzymes causing damage to the tissue. 28,29 The histopathological studies showed that DENA treatment caused complete distortion of liver histology and led to proliferation of bile ducts, anisocytosis, anisokaryosis and karyomegaly. The infiltration of inflammatory cells was also observed along with the degenerative changes.…”
Section: Discussionmentioning
confidence: 99%